Optimising antimicrobial stewardship interventions in English primary care: a behavioural analysis of qualitative and intervention studies - Borek, A; Wanat, M; Atkins, L; Sallis, A; Ashiru-Oredope, D; Beech, E; Butler, C; Chadborn, T; Hopkins, S; Jones, L; McNulty, C; Roberts, N; et al. (BMJ Publishing Group, 2020)
Objective While various interventions have helped reduce antibiotic prescribing, further gains can be made. This study aimed to identify ways to optimise antimicrobial stewardship (AMS) interventions by assessing the extent to which important influences on antibiotic prescribing are addressed (or not) by behavioural content of AMS interventions.